Analysis of Reading Skills Using The Mahāratul Qirāah Method in Fullday Class at SMA Muhammadiyah Gading Rejo School Year 2023/2024 - Qodari, Salma Lailatul; Muhtarom, Muhtarom; Masrur, Moh.; Sari, Ruly Nadian (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2024)
Arabic plays an important role, especially for Muslims. Arabic is the language of science, both strict science and different science. Learning Arabic, with its various qualities and inspiration for studying it among the community, turns out to have obstacles and problems that must be faced because Arabic is not an easy language to master completely. This research aims to understand the mahāratul qirāah learning methodology, find out and study mahāratul qirāah skills, and find out the supporting and inhibiting factors for mahāratul qirāah abilities in students in full-day classes at SMA Muhammadiyah Gading Rejo. The type of research applied in this study is descriptive qualitative. The data sources applied in this study are primary and secondary data. Several methods for collecting data, including observation, interviews, and documentation. The results of the study show that the methodology used by Arabic language teachers at SMA Muhammadiyah Gading Rejo is the qirāah jahriyah method. Students still have several difficulties in learning Arabic, such as difficulty in distinguishing the meaning of letters that are mutashābihat (similarity), lack of fluency in reading Arabic texts, and less precise use of reading Arabic texts. Supporting factors in learning Arabic, especially for mahāratul qirāah, include the enthusiasm of teachers in teaching and students in learning, good interaction between teachers and students. The inhibiting factors include class conditions that are not conducive, there are some students who are unable to read Arabic texts and the Koran, and limited time for teachers to guide them during teaching and learning activities.